Լռությունը՝ որպես ենթատեքստ - Լ. Մ. Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
Вслух сказанное слово принято считать текстом, а молчание – подтекстом, который также имеет свои подтексты. Сущность этих подтекстов рассматривается не только с философской и логической точек зрения, но и с позиции психологии. Выявление генетических причин и гносеологического значения молчания не умаляет значения слова и общения посредством речи, при этом отдается предпочтение молчанию как своеобразному виду общения, поскольку молчание также являет собой вид коммуникации, богатый подтекстами. Следует добавить, что молчание порою бывает красноречивее слова. Although the aloud recited word is regarded as a text and the silence as a subtext, it also, in its turn, has own subtexts. The essence of these subtexts is considered not only from philosophical and logical points of view but also from position of psychology. The revelation of genetic reasons and gnosiological meaning of silence do not reduce the meaning of the word and communication by means of speech, by which the preference is given to the silence as a peculiar kind of communication, rich in contexts. Thus the silence is sometimes more expressive than any kind of speech. What was said above is confirmed by examples from fiction, poetry and also through expressions of ancient thinkers and philosophers.
Keywords: B Philosophy; Psychology; Religion; B Philosophy